Advances in improving fertility in women through stem cell-based clinical platforms. (4th May 2017) - Vanni, Valeria Stella; Viganò, Paola; Papaleo, Enrico; Mangili, Giorgia; Candiani, Massimo; Giorgione, Veronica
ABSTRACT: Introduction : Due to their regenerative ability, stem cells are looked at as a promising tool for improving infertility treatments in women. As the main limiting factor in female fertility is represented by the decrease of ovarian reserve, the main goals of stem cell-based clinical platforms would be to obtain in vitro or in vivo neo-oogenesis. Refractory endometrial factor infertility also represents an obstacle for female reproduction for which stem cells might provide novel treatment strategies. Areas covered : A systematic search of the literature was performed on MEDLINE/PubMed database to identify relevant articles using stem-cell based clinical or research platforms in the field of female infertility. Expert opinion : In vitro oogenesis has not so far developed beyond the stage of oocyte-like cells whose normal progression to mature oocytes and ability to be fertilized was not proved. Extensive epigenetic programming of gamete precursors and the complex interactions between somatic and germ cells required for human oogenesis likely represent the main obstacles in stem-cell-based neo-oogenesis. Also resuming oogenesis in vivo in adulthood still appears a distant hypothesis, as there is still a lack of consensus about the existence and functionality of adult ovarian stem cells.